The effects of irradiation on bone fracture healing: can it pronote mineralization at low doses? - Heybeli, Nurettin. (Thesis (M.S.)-Bogazici University. Institute of Biomedical Engineering, 2010., 2010)
Non-union, or delayed union of a bone fracture poses a major burden both to the individual and society. This experimental study investigated the hypothesis that low dose irradiation can enhance fracture healing and mineralization. Standardized transverse femur fractures were created and intramedullary xed with an open technique to forty young adult, male Sprague-Dawley rats and randomized to RT (irradiation with 1 Gy) and C (controls, sham treatment) groups. At third and sixth week after fracture, high resolution Bone Mineral Density (BMD) analysis, bone scintigraphy and radiographic examination with a mammography device were performed to subgroups (RT3, C3, ve RT6, C6) and rats were sacri ced for histopathological examinations. Statistically signi cant di erences were found at sixth week; as BMD index was found to be higher in RT group (p = 0.006) and BMD value was found lower in the non-fractured regions of the irradiated femurs (p = 0.005). No statistically signi cant di erences were found between groups for other parameters. Lamellar bone formation was disorganized at group RT6 when compared with controls by histopathological examinations. The results showed increased mineralization at the fracture site only when compared with irradiated non-fractured bone region, which cannot be regarded as a basis for clinical practice. However, when applications like heterotopic ossi cation prophylaxis are considered, the issue remains to be solved by molecular techniques, speci cally for doses between 1 and 5 Gy.|Keywords: Irradiation, fracture healing, bone mineral density, bone scintigraphy.
Keywords: Irradiation.; Healing.